Epitope mapping of allergen ovalbumin using biofunctionalized magnetic beads packed in microfluidic channels The first step towards epitope-based vaccines - Jankovicova, Barbora; Rosnerova, Sarka; Slovakova, Marcela; Zverinova, Zuzana; Hubalek, Martin; Hernychova, Lenka; Rehulka, Pavel; Viovy, Jean-Louis; Bilkova, Zuzana (Journal of chromatography. A, 2008)
Specific allergen immunotherapy is frequently associated with adverse reactions. Several strategies are being developed to reduce the allergenicity while maintaining the therapeutic benefits. Peptide immunotherapy is one such approach. Methods for the simple and rapid identification of immunogenic epitopes of allergens (i.e. allergenic epitopes) are ongoing and could potentially lead to peptide-based vaccines. An epitope extraction technique, based on biofunctionalized magnetic microspheres self-organized under a magnetic field in a channel of a simple microfluidic device fabricated from polydimethylsiloxane, was applied in the isolation and identification of prospective allergenic epitopes. Similarly to chromatographic column separations, the easily replaceable plug of self-organized beads in the channel benefits especially from an even larger surface-to-volume ratio and an enhanced interaction of the surfaces with passing samples. Ovalbumin, the major protein of egg white and a typical representative of food allergens, was selected as the model molecule. Highly resistant ovalbumin was at first efficiently digested by a magnetic proteolytic reactor with trypsin treated with l-1-tosylamido-2-phenylethyl chloromethyl ketone and the second step, i.e. capture of allergenic epitopes from the mixture of peptides, was performed by a magnetic immunoaffinity carrier with orientedly immobilized rabbit anti-ovalbumin IgG molecules. Captured peptides were released with 0.05% trifluoroacetic acid. The elution fractions were analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The peptide fragment of ovalbumin HIATNAVLFFGR (m/z: 1345.75, position: 371-382) was identified as a relevant allergenic epitope in this way. Such a microfluidic magnetic force-based epitope extraction technique applied in the epitope mapping of ovalbumin has the potential to be a significant step towards developing safe and cost-effective epitope-based vaccines.
Keywords: Mass Spectrometry; Immunomagnetic Separation; Allergens; ovalbumin; Epitopes; Epitope Mapping; vakcíny; potravinová alergie; imunomagnetická separace; epitopy; Ovalbumin; alergeny; Microfluidic Analytical Techniques; mikrofluidní analytické techniky; Microspheres; Vaccines; mapování epitopu; mikrosféry; Food Hypersensitivity; hmotnostní spektrometrie